Regulation of the ER Stress Response by the Ion Channel Activity of the Infectious Bronchitis Coronavirus Envelope Protein Modulates Virion Release, Apoptosis, Viral Fitness, and Pathogenesis - Li, Shumin; Yuan, Lixia; Dai, Guo; Chen, Rui Ai; Liu, Ding Xiang; Fung, To Sing (Frontiers in Microbiology, 2020)
Coronavirus (CoV) envelope (E) protein is a small structural protein critical for virion morphogenesis and release. The recently characterized E protein ion channel activity (EIC) has also been implicated in modulating viral pathogenesis. In this study, we used infectious bronchitis coronavirus (IBV) as a model to study EIC. Two recombinant IBV harboring EIC-inactivating mutations – rT16A and rA26F were serially passaged, and several compensatory mutations were identified in the transmembrane domain (TMD). Two recombinant IBVs (rIBVs) harboring these putative EIC-reverting mutations – rT16A/A26V and rA26F/F14N were recovered. Compared with the parental rIBV-p65 control, all four EIC mutants exhibited comparable levels of intracellular RNA synthesis, structural protein production, and virion assembly. Our results showed that the IBV EIC contributed to the induction of ER stress response, as up-regulation of ER stress-related genes were markedly reduced in cells infected with the EIC-defective mutants. EIC-defective mutants also formed smaller plaques, released significantly less infectious virions into the culture supernatant, and had lower levels of viral fitness in cell culture. Significantly, all these defective phenotypes were restored in cells infected with the putative EIC revertants. EIC mutations were also implicated in regulating IBV-induced apoptosis, induction of pro-inflammatory cytokines and viral pathogenicity in vivo. Taken together, this study highlights the importance of CoV EIC in modulating virion release and various aspects of CoV-host interaction.